Protective coating composition, treatment method using the same, and article thereof

By developing an alkaline protective coating composition that does not contain organic solvents, the composition can react with the surface of the light metal material to form a protective coating, solving the problem of difficult to provide good corrosion protection in the prior art, and achieving improved adhesion and corrosion resistance.

CN119546716APending Publication Date: 2025-02-28HENKEL KGAA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280098033.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat the surface of light metal materials in the domestic and construction fields and in the automotive industry, providing good corrosion protection, while avoiding the use of strong acids, large amounts of organic solvents and high fluoride concentrations.

Method used

An alkaline protective coating composition is developed, which contains no organic solvents, combines the properties of pretreatment and primer, and can react directly with metal substrates to form a very thin protective coating, improving adhesion and corrosion resistance.

Benefits of technology

Improved adhesion and good corrosion resistance are achieved, capable of meeting T-bend requirements of equal to or less than 1T, no additional primer is required, and good performance is maintained under aging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234677960000151
    Figure BDA0005234677960000151
  • Figure BDA0005234677960000161
    Figure BDA0005234677960000161
  • Figure BDA0005234677960000201
    Figure BDA0005234677960000201
Patent Text Reader

Abstract

The present invention relates to a protective coating composition comprising a) at least one resin selected from the group consisting of a polyurethane resin (A), a polyurethane-acrylic resin (B); b) a solvent; c) a bifunctional epoxy resin precursor (C) represented by the following formula: R1-Y-[CH2-CH (OH)-R3-CH (OH)-CH2-X-R4-X] n-R2, and a method for preparing the same. The invention also provides a method for treating a metal surface by using the protective coating composition. The invention also relates to an article having at least a portion of a surface treated with the protective coating composition, exhibiting improved corrosion resistance, adhesion and anti-aging adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a protective coating composition and a method for treating the surface of a metal substrate coated with zinc or a zinc alloy, or coated with aluminum or an aluminum alloy by means of the protective coating composition. It is particularly suitable for the surface treatment of coil coatings for use in the domestic and construction fields and in the automotive industry. Articles comprising such metal substrate surfaces treated with the protective coating composition show improved adhesion and good corrosion resistance. Background of the Invention

[0003] Among the metal materials in actual use, light metal materials such as aluminum and magnesium are the lightest and have high specific strength, so they have been widely used in various fields, such as interior and exterior parts of automobiles and two-wheelers, household accessories, containers for storage (such as bags and suitcases), sports equipment, optical instruments and tool parts, sticks, and other emerging fields in the electronics industry (such as computers, audio, etc.). However, light metal materials are the most active metal materials and are difficult to use directly without any treatment due to their low corrosion resistance.

[0004] In the household and construction sectors as well as in the automotive industry, there is a growing demand for sheet metal with a pre-applied coating, which facilitates, for example, mechanical processing such as punching, drilling, folding, profiling and / or deep drawing. Such pre-applied coatings must not only impart corrosion-inhibiting properties to the sheet metal, but also facilitate mechanical processing. Another function of such pre-applied coatings is to lay the foundation for the subsequent decorative topcoat layer. Workpieces produced by mechanical processing of sheet metal pre-coated in this way can then be coated with a topcoat.

[0005] According to the prior art, the coil coating process consists essentially of three sub-steps. In the first step, the metal sheet is cleaned and coated with an inorganic pre-treatment layer; in the second step, a primer is applied; and in the final third step, a topcoat is applied. In certain applications, a clear lacquer / varnish or a protective film coating may also be applied. Attempts have been made to provide those functions that contribute to the above-mentioned purpose of the pre-applied coating only through the pre-treatment step.

[0006] For example, suitable organic polymers are added to the inorganic conversion process for this purpose, which polymers are capable of forming a surface film exhibiting the desired functional properties of the pre-applied coating.

[0007] DE19923118A1 discloses a polymerizable composition for an organic coating of a metal substrate, and a method for protecting a steel substrate by an organic / inorganic hybrid polymer film based on an alkoxysilane, another condensable organometallic compound of the formula M(OR)4 and (meth)acrylic acid, water and a polymerization initiator. The coating is cured by thermal polymerization or photopolymerization. Zirconium and titanium are mentioned as metals of the organometallic compound. It is stated herein that this film protects the steel substrate from corrosion and oxidation, and that the coating is also intended to protect the substrate from impacts and other mechanical effects.

[0008] DE19751153A discloses polymerizable compositions containing titanium, manganese and / or zirconium salts of ethylenically unsaturated polymerizable carboxylic acids and other ethylenically unsaturated comonomers and free radical polymerization initiators, which are suitable for organic coil coating of metal materials. These non-aqueous metal coatings are suitable for chromium-free pretreatment of steel and have good corrosion control.

[0009] DE 197 54 108 A1 describes a chromium-free aqueous anticorrosion composition for the treatment of galvanized or alloy-galvanized steel surfaces and aluminum surfaces. The agent is particularly suitable for treating metal strips to protect them from corrosion, with or without subsequent painting, and is preferably applied to the surface in such a way that a dry layer coating is produced.

[0010] Despite the extensive prior art, there remains a need for improved corrosion inhibitors and metal surface coating methods that enable chromium-free pretreatment of metal substrates that provide good corrosion protection while avoiding strong acids, large amounts of organic solvents, and high fluoride concentrations.

[0011] Therefore, an object of the present invention is to provide a surface protective coating composition for light metal materials (particularly aluminum, zinc or alloys thereof) which can eliminate the problems associated with conventional surface treatment compositions. Summary of the invention

[0012] The present invention relates to a protective coating composition, which is alkaline and may not contain organic solvents. The protective coating composition combines the properties of pretreatment and primer, has good adhesion, and further shows improved anti-corrosion properties. The protective coating composition can directly react with a metal substrate to form a very thin protective coating with a thickness of 0.5-4.0 microns, preferably 1.0-3.0 microns, preferably 1.0-2.0 microns. The protective coating is a cured product of the protective coating composition, which provides good adhesion between the metal substrate and the topcoat, so that the treated substrate can meet a T bend value (new) equal to or less than 1T without any additional primer, and can meet molding requirements. In addition, after the treated substrate is aged for 24 hours at a temperature of 50±2°C and a humidity of 95%, when tested according to the GB / T13448-2006 standard, it can meet a T bend value (aged) equal to or less than 2T. The substrate is preferably a galvanized steel coil, and the treated substrate is preferably used as a color-coated coil.

[0013] Furthermore, the coating composition according to the invention is preferably used as a two-in-one primary coating as pretreatment and primer, followed by the immediate application of the topcoat layer in a coil coating plant. In this case, the metal sheet is sent for further processing only after it has been completely coated. This saves the primer application step and the subsequent baking step compared to conventional coil coating methods.

[0014] The present invention relates to a protective coating composition comprising:

[0015] a) at least one resin selected from the group consisting of a polyurethane resin (A) and a polyurethane-acrylic resin (B);

[0016] b) solvent; and

[0017] c) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula:

[0018] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2

[0019] Among them, independently,

[0020] X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;

[0021] Y=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;

[0022] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H;

[0023] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms;

[0024] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4;

[0025] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;

[0026] n is an integer of 1 to 10.

[0027] The present invention also relates to a method for treating a metal surface by using the protective coating composition according to the present invention, the method comprising the following steps:

[0028] a) contacting the protective coating composition according to the present invention with a metal surface at a process temperature of at least 40° C. but not higher than 200° C., thereby forming a film on the metal surface;

[0029] b) optionally removing excess protective coating composition from the surface; and

[0030] c) curing the film on the surface by thermal means or high energy irradiation at a process temperature of 50° C. to 90° C. for at least 10 −5 seconds to form a cured coating.

[0031] The present invention also relates to an article, at least a portion of which comprises a treated surface according to the present invention. The present invention also relates to an article, at least a portion of which comprises a protective coating, which is the cured product of the protective coating composition according to the present invention. The layer thickness of the protective coating is at least 0.5 μm, but not more than 4.0 μm. DETAILED DESCRIPTION

[0032] In the following paragraphs, the present invention will be described in more detail. Each aspect described in this way can be combined with any other aspect or aspects, unless there is a clear indication to the contrary. In particular, any feature indicated as being preferred or advantageous can be combined with any other one or more features indicated as being preferred or advantageous.

[0033] In the context of the present invention, unless the context requires otherwise, the terms used are to be interpreted according to the following definitions.

[0034] As used herein, the singular forms "a," "an," and "the" include both singular and plural references unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" generally includes "and / or" in its meaning unless the context clearly dictates otherwise.

[0035] As used herein, the terms "comprising", "comprises" and "comprised of" are synonymous with "including", "includes" or "containing" and are inclusive or open-ended and do not exclude other unrecited members, elements or process steps.

[0036] The recitation of numerical endpoints includes all numbers and fractions subsumed within the corresponding ranges, as well as the recited endpoints.

[0037] Unless otherwise defined, all terms used in the disclosure of the present invention, including technical and scientific terms, have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs. By way of further guidance, term definitions are included in this specification for a better understanding of the teachings of the present invention.

[0038] In the context of this disclosure, several terms will be used.

[0039] The term "polymer" is used herein in accordance with its common usage in chemistry. A polymer is composed of many repeating subunits. The term "polymer" is used to describe the resulting material formed by a polymerization reaction.

[0040] Unless the context requires otherwise, the terms aluminum or zinc as used herein include pure metals and alloys, hereinafter referred to simply as "aluminum" or "zinc".

[0041] The terms "mass" and "weight" are used synonymously herein. Therefore, unless otherwise specified, "weight percent" (wt%) refers to the mass content percentage based on the mass (weight) of the entire composition or based on all molecules.

[0042] As used herein, "primary coating" means that the metal substrate has not been subjected to any other protective treatment before contacting with the protective coating composition according to the present invention. In fact, the protective coating composition according to the present invention should be applied to a freshly prepared or freshly cleaned dry metal surface. This treatment represents the primary or only protective measure for the metal substrate. After application of the protective composition according to the present invention, additional decorative and / or anti-corrosion coatings may be superimposed, such as conventional dip-painting, spray-painting or powder coating. The primary coating of the present invention applies a thin protective coating on the metal substrate, acting as a two-in-one coating of pretreatment and primer.

[0043] A newly prepared or newly cleaned metal surface without any protective measures is contacted with the protective coating composition according to the present invention, the protective coating composition is cured, and a protective coating is formed on the surface of the metal sheet. In this way, the treated metal surface obtained has a primary protective coating. The metal sheet can be stored and / or transported in this form. In addition, it can also be cut into blocks, optionally shaped, and joined to other blocks to form structural units. The metal surface that has been coated with the protective coating composition according to the present invention can also be commercialized and further processed without depositing additional coatings on the protective coating. Depending on the final end use, once the final metal object is manufactured, additional decorative coatings can be applied.

[0044] Alternatively, the surface of the metal sheet coated with the protective coating composition according to the present invention, or the metal sheet cut therefrom, can be coated with at least one additional decorative coating or anti-corrosion coating, such as a topcoat, before these metal sheets are commercialized and / or further processed into subassemblies. In this case, the protective coating according to the present invention is used as a combination of "pretreatment" and "primer". The protective coating also provides good adhesion between the subsequent decorative topcoat and the metal substrate, and for color-coated sheets, this good adhesion can meet the molding requirements in subsequent operations. Therefore, it can reduce some failure conditions, such as paint film powdering, blistering, cracking, etc.

[0045] Protective coating composition

[0046] The present invention relates to a protective coating composition, which comprises a solvent; a bifunctional epoxy resin precursor (C); an optional polyacrylic-epoxy resin (D); and a resin selected from the group consisting of a polyurethane resin (A) and a polyurethane-acrylic resin (B). In some embodiments, the protective coating is an aqueous dispersion.

[0047] Polyurethane resin (A)

[0048] The polyurethane resin (A) used in the present invention can be prepared by subjecting an organic compound (polyol) having two or more hydroxyl groups in its molecule to polyaddition reaction with polyisocyanate, chain extension with diamine or the like, and dispersion in water.

[0049] The polyol is not particularly limited as long as it contains two or more hydroxyl groups in its molecule. As the polyol, polycarbonate polyol and polyester polyol are preferred. More specifically, the polyurethane resin (A) is preferably in the form of a polycarbonate-based polyurethane or a polyester-based polyurethane.

[0050] Polycarbonate polyols can be prepared by reacting carbonate compounds with diols. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, diethylene carbonate, etc. Examples of diols include aliphatic diols that can be substituted with lower alcohols; alicyclic diols, such as cyclohexanediol, hydrogenated xylene glycol, etc.; and aromatic diols, such as xylene glycol, etc. Among these diols, aliphatic diols are preferred, and aliphatic diols having a carbon chain length of not less than 4 and not more than 9 are more preferred, such as 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, etc.

[0051] Polyester polyols can be prepared by condensing low molecular diols and dicarboxylic acids. Examples of low molecular diols include diols having not less than 2 and not more than 6 carbon atoms, such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, etc. Among these low molecular diols, ethylene glycol, propylene glycol, 1,4-butanediol, etc. are preferred. Examples of dicarboxylic acids include aliphatic dibasic acids, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, tridecanedioic acid, etc.; and aromatic dibasic acids, such as isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc. Among these dicarboxylic acids, aliphatic dibasic acids are preferred, and dibasic acids having a methylene chain length of not less than 4 and not more than 8 are more preferred, such as adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, etc.

[0052] Examples of polyisocyanates include chain aliphatic diisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, etc.; aliphatic diisocyanates having a cyclic structure such as isophorone diisocyanate, hydrogenated xylene diisocyanate, dicyclohexylmethane 4,4'-diisocyanate, etc.; aliphatic diisocyanates containing aromatic rings such as xylene diisocyanate, tetramethylxylene diisocyanate, etc.; aromatic diisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, etc.; and modified products of these diisocyanates (e.g., modified products containing carbodiimide, uretdione, and uretimine, etc.), etc. Among these polyisocyanates, preferred are aliphatic diisocyanates and aromatic diisocyanates.

[0053] The polyurethane resin (A) is preferably used in the form of an aqueous dispersion thereof. If necessary, the aqueous dispersion of the polyurethane resin (A) may further contain a dispersant such as a surfactant.

[0054] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion. In some embodiments, the polyurethane resin (A) preferably contains an acid group from the perspective of improving its dispersion stability in an aqueous medium and from the perspective of improving the storage stability of the aqueous dispersion and the adhesion properties and optical density of the aqueous dispersion. As the acid group of the polyurethane resin (A), a carboxyl group is preferred from the perspective of improving the storage stability of the aqueous pigment dispersion and the adhesion properties and optical density of the aqueous ink.

[0055] The polyurethane resin (A) containing a carboxyl group can be prepared by subjecting a polyol, a polyisocyanate and a dialkanol carboxylic acid to an addition polymerization reaction. Examples of dialkanol carboxylic acids include dimethylol butanoic acid, dimethylol propionic acid and salts of these acids, etc. Examples of reaction solvents for the above-mentioned addition polymerization reaction include acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, ethyl acetate, toluene, xylene, etc. In the above-mentioned addition polymerization reaction, if necessary, a chain extender or a reaction terminator can also be used in combination with the above-mentioned components. By using a chain extender, the molecular weight of the resulting resin can be increased. As a chain extender, polyols and polyamines can be used. In addition, as a reaction terminator, monohydric alcohols and monoamines can be used.

[0056] Most or even all of the polyurethane resins contained in the protective coating composition preferably have carboxyl groups. The carboxyl groups are optionally neutralized and reacted, in particular with ammonia, amines (in particular alkanolamines) or / and alkali metal compounds, to form an aqueous solution with the polyurethane synthetic resin, which can be easily dispersed with water, and the carboxyl groups are optionally insoluble in water before reaction under standard conditions. The neutralization of the -COOH groups is an anionic stabilization reaction. It may also be necessary to additionally add at least one emulsifier and / or at least one protective colloid (as an additive within the scope of the present application) to stabilize the dispersion of the polyurethane synthetic resin and the protective coating composition.

[0057] In the preparation process of the present invention, the pH value of the aqueous coating composition without adding other compounds may preferably be greater than 7 to 12, particularly preferably greater than 7 to 11, 7.5 to 10.5, or 8 to 9.5. It should be noted that the polyurethane resin is usually neutralized by the manufacturer, for example, during the polymerization process. In the aqueous preparation without adding other compounds, the pH value of the aqueous coating composition is preferably 1 to 12. If the pH value of the aqueous composition changes to a value outside the range of greater than 7 to 11 during the preparation of the aqueous composition, it is recommended to restore it to a pH range greater than 7 to 11 by appropriate addition but preferably only adding at least one alkaline substance, or even to a narrower working range within this range, because salts may be undesirably formed when adding acids and / or acidic substances. If the pH value drops due to the storage of the synthetic resin or / and the mixture, it may be helpful to restore the pH value (especially the pH value of the aqueous coating composition ready for use) to a more alkaline range by adding, for example, sodium hydroxide aqueous solution.

[0058] In some embodiments of the present invention, the polyurethane resin has a glass transition temperature (Tg) of -100°C to -50°C, or -100°C to -70°C, and an elongation of 300% or more, or 500% or more.

[0059] In some embodiments of the present invention, the weight average molecular weight of the polyurethane resin may be at least 2,000, preferably 5,000-250,000, and particularly preferably 20,000-200,000.

[0060] In some embodiments of the present invention, based on the total weight of the solid content in the protective coating composition, the content of the polyurethane resin in the protective coating composition is 60 wt % to 85 wt %, or 65 wt % to 80 wt %, or 70 wt % to 85 wt %. The lower limit concentration of the polyurethane resin in the protective coating composition is 60 wt %, 65 wt % or 70 wt %. The upper limit concentration of the polyurethane resin is 85 wt %, or 80 wt %, or 75 wt %.

[0061] As used herein, “M w ” refers to the weight average molecular weight and is the theoretical value as determined by gel permeation chromatography (GPC) relative to linear polystyrene standards ranging from 1.1 M to 580 Da, which can be performed using a Waters 2695 Separations Module and a Waters 2414 Differential Refractometer (RI detector).

[0062] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion, and the polyurethane resin includes polyether-based polyurethane resins and polyester-based polyurethane resins.

[0063] Examples of commercially available polyurethane resins are, for example, Leasys 3900 or Leasys 5531 from Wanhua Chemical, K200 polyurethane resin from Anhui Andahuatai materials.

[0064] The above-mentioned polyurethane resins may be used alone or in any combination.

[0065] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion, and the polyurethane resin includes a polycarbonate-based polyurethane resin.

[0066] Examples of commercially available polycarbonate resins are, for example, Hauthane L-3528 and L-3529 from Hauthaway, Esacote PU A32D and ESACOTE PU 6419 from Lamberti.

[0067] The above-mentioned polyurethane resins may be used alone or in any combination.

[0068] Polyurethane-acrylic resin (B)

[0069] In some embodiments, the polyurethane-acrylic resin (B) is an aqueous dispersion of a polyurethane-acrylic resin.

[0070] Polyurethane-acrylic resin can be directly synthesized according to known methods, or can be commercially available. For example, acrylic-urethane dispersion can be prepared by polyol, acid, isocyanate and acrylate reaction. Polyol can be one or more selected from the group consisting of the following: polybutylene glycol (PTMG), 1,6-hexanediol, ethylene glycol, propylene glycol, diethylene glycol, butanediol (butylene glycol), neopentyl glycol, trimethylolpropane, butanediol (butanediol), 1,4-hexanediol and 3-methylpentanediol. The acid can be one or more selected from the group consisting of the following: dimethylolpropionic acid (DMPA), acrylic acid and adipic acid, phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, adipic acid, fumaric acid, maleic acid, trimellitic acid, malic acid and aconitic acid. In addition, the isocyanate may be one or more selected from the group consisting of isophorone diisocyanate (IPDI), trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, propylene diisocyanate, ethylene diisocyanate, 2,3-dimethylethylene diisocyanate, 1-methyltrimethylene diisocyanate, 1,3-cyclopentylene diisocyanate, 1,4-cyclopentylene diisocyanate, 1,2-cyclopentylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, oligomeric isocyanates, isophorone diisocyanate, 4,4-diphenylpropane diisocyanate, xylene diisocyanate, and 1,1,6,6-tetramethylhexamethylene diisocyanate. The acrylic acid ester may include monounsaturated esters of (meth)acrylic acid and unsubstituted alkyl groups, and particularly preferably methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, 3,3,5-trimethylhexyl (meth)acrylate, stearyl (meth)acrylate, dodecyl (meth)acrylate, cycloalkyl (meth)acrylate. Suitable monounsaturated esters of (meth)acrylic acid and substituted alkyl groups may preferably be substituted with one or more hydroxyl groups, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. The total mass of the (meth)acrylate preferably has a content of 5.0 to 70.0 wt %, more preferably 30.0 to 50.0 wt %, based on the total weight of the urethane-acrylic resin (B).Also, the (meth)acrylate should be selected so that the glass transition temperature Tg of the obtained polyurethane-acrylic resin (B) is 5°C to 45°C, preferably 10°C to 40°C.

[0071] In some embodiments, the polyurethane-acrylic resin (B) preferably includes a mixed or cross-linked (meth)acrylic resin and a polyurethane resin.

[0072] It is more preferred that the acid groups contained in the (meth)acrylic resin and the urethane resin are partially cross-linked with the cross-linking agent.

[0073] In some embodiments of the present invention, the aqueous dispersion of polyurethane-acrylic resin comprises polyester-polyurethane-poly(meth)acrylate, polyester-polycarbonate-polyurethane-polyacrylate, and corresponding derivatives.

[0074] In some embodiments of the present invention, the content of the polyurethane-acrylic resin in the protective coating composition is 50 wt % to 85 wt %, or 55 wt % to 80 wt %, or 60 wt % to 75 wt %, based on the total weight of the solid content in the protective coating composition. The lower limit concentration of the polyurethane-acrylic resin in the protective coating composition is 50 wt %, or 55 wt %, or 60 wt %. The upper limit concentration of the polyurethane resin is 85 wt %, or 80 wt %, or 75 wt %.

[0075] Examples of commercially available polyurethane-acrylic resins are, for example, BS PUAW Tt-10 and SGR-0215W from Shanghai Xinyang Chemical, or SGR-3002W from Changle Chemical, or Neopac E-123 and Neopac E-129 from DSM.

[0076] The above-mentioned polyurethane-acrylic resins may be used alone or in any combination.

[0077] In some embodiments of the present invention, the above-mentioned polyurethane-acrylic resin (B) and polyurethane resin (A) can be used alone or in any combination. In some embodiments of the present invention, based on the total weight of the solid content in the protective coating composition, the content of polyurethane-acrylic resin (B) and / or polyurethane resin (A) in the protective coating composition is 50 wt % to 85 wt %, or 55 wt % to 80 wt %, or 60 wt % to 75 wt %. The lower limit concentration of the resin in the protective coating composition is 50 wt %, or 55 wt %, or 60 wt %, or 65 wt %. The upper limit concentration of the resin is 85 wt %, or 80 wt %, or 75 wt %, or 70 wt %.

[0078] Bifunctional epoxy resin precursor (C)

[0079] The difunctional epoxy resin precursor (C) of the present invention can be commercially obtained or prepared by a known method, for example, by reacting a difunctional epoxy compound with a nucleophilic or electrophilic compound having an active hydrogen atom.

[0080] In some embodiments of the present invention, the difunctional epoxy resin can be reacted with a polymer having a hydroxyl group (-OH), a polymer having an ester group (-COOR), an organic / inorganic acid containing a heteroatom (N, S, P), or an amino compound to prepare a difunctional epoxy resin precursor (C).

[0081] The epoxy compound used in the preparation is not particularly limited in type as long as it contains at least two epoxy groups in its molecule.

[0082] The two epoxy groups can generate two hydroxyl groups of the bifunctional epoxy resin precursor (C).

[0083] The difunctional epoxy compound comprises bisphenol A epoxy, bisphenol F epoxy, acryl (acryl) modified epoxy, epoxy ester obtained by epoxy and unsaturated fatty acid reaction, carbamate modified epoxy, silane modified epoxy, halogenated epoxy alkane (e.g. epihalohydrin), phosphoric acid modified epoxy resin, and the epoxy compound with two or more glycidyl groups. Above-mentioned epoxy resin can be used alone, also can two or more combinations be used. The epoxide equivalent weight of epoxy resin of the present invention is from about 100 grams / equivalent to about 2000 grams / equivalent.

[0084] The rigidity and appropriate flexibility of the polyhydroxyl and heteroatom structural units derived from the difunctional epoxy resin precursor (C) can improve the adhesion of the coating composition. In addition, this structure is difficult to hydrolyze, and can improve adhesion, and can also improve the corrosion resistance of the coating composition. The hydroxyl groups in the dihydroxy functionalized epoxy resin precursor can be firmly bonded to the metal substrate due to its polarity, and help to improve the adhesion to the metal substrate. In addition, the heteroatom structure (OC, NC, SC, PC) also helps to establish a firm bond with the metal substrate. During the processing of the coating composition, the hydroxyl groups in the epoxy resin precursor (C) are cross-linked with the zirconium compound and the compound containing the silanol group, thereby improving the chemical resistance and corrosion resistance of the coating.

[0085] The epoxy resin precursor (C) is preferably used in the form of an aqueous dispersion thereof. If necessary, the aqueous dispersion of the bifunctional epoxy resin precursor (C) may further contain a dispersant such as a surfactant.

[0086] The weight average molecular weight of the bifunctional epoxy resin precursor (C) is preferably 200 to 10,000.

[0087] The pH value of the bifunctional epoxy resin precursor (C) is not particularly limited, but a preferred pH value is 6 to 9 in view of improving stability and corrosion resistance.

[0088] The content ratio of the bifunctional epoxy resin precursor (C) to the total mass of the solid content is preferably 4.5 to 40 wt%, or 4.5 to 35 wt%, or 10 to 30 wt%, or 10 to 25 wt%, or 8.5 to 18.5 wt%. If the solid content ratio is less than 4 wt%, or less than 4.5 wt%, the T-bend test cannot be passed; and if the solid content ratio exceeds 30 wt%, or exceeds 23 wt%, the chemical resistance will be negatively affected.

[0089] The content ratio of the bifunctional epoxy resin precursor (C) to the total mass of the resin (including the polyurethane-acrylic resin (B), the polyurethane resin (A), the polyacrylic-epoxy resin (D) and the bifunctional epoxy resin precursor (C)) is preferably 7.0 wt% to 30 wt%, or 10.0 wt% to 28 wt%, or 10.5 wt% to 27 wt%, or 10.5 wt% to 26 wt%. If the content ratio is less than 7 wt%, or less than 10.5 wt%, the T-bend test cannot be passed; and if the content ratio exceeds 25 wt%, or exceeds 30 wt%, the chemical resistance will be negatively affected.

[0090] In some embodiments, the epoxy resin may be reacted with a polymer having a functional group, an organic / inorganic acid having a heteroatom (N, S, P), and an amino group to produce a difunctional epoxy resin precursor.

[0091] In some embodiments, bisphenol A epoxy is reacted with orthophosphoric acid and propylene glycol monomethyl ether to produce a phosphoric acid-modified epoxy resin.

[0092] In some embodiments, bisphenol A epoxy is reacted with citric acid and propylene glycol monomethyl ether to produce a carboxyl group-modified epoxy resin.

[0093] In some embodiments, the difunctional epoxy resin precursor has the formula:

[0094] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2

[0095] Among them, independently,

[0096] X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; preferably -COO-, -P(OR)(OH)-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- contains an aliphatic chain having 1 to 5 carbon atoms;

[0097] Y = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; preferably -COO-, -P(OR)(OH)-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- contains an aliphatic chain having 1 to 5 carbon atoms;

[0098] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H; preferably 1 to 10 carbon atoms or H;

[0099] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms; preferably 1 to 10 carbon atoms;

[0100] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4; preferably 1 to 10 carbon atoms;

[0101] R3 is any type of chain as long as it connects two hydroxyl α-carbon atoms; preferably, R3 is selected from the group consisting of: aromatic or aliphatic groups having 1 to 20 carbon atoms, polyurethane groups, aliphatic or aromatic alkanes having 2 to 20 carbon atoms, and acrylate-containing polymer groups.

[0102] n is an integer of 1-10, preferably an integer of 2-8.

[0103] In some embodiments, the difunctional epoxy resin precursor has the formula:

[0104] HX-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H,

[0105] Among them, independently,

[0106] X=-COO-, -P(OR)(OH)-O-;

[0107] R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms;

[0108] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;

[0109] n is an integer of 2-8.

[0110] Polyacrylic-epoxy resin (D)

[0111] The protective coating composition of the present invention further comprises a polyacrylic-epoxy resin (D).

[0112] In some embodiments of the present invention, the polyacrylic-epoxy resin (D) is an aqueous dispersion.

[0113] In some embodiments of the present invention, the polyacrylic-epoxy resin (D) of the present invention includes a carboxyl group-containing polymer, which contains repeating units derived from a carboxyl group-containing vinyl monomer. In other words, the polyacrylic-epoxy resin (D) contains a carboxyl group-containing polymer chain as part of the structure.

[0114] The glass transition temperature (Tg) of the waterborne polyacrylic-epoxy resin (D) is not particularly limited, and is preferably 50° C. to 100° C. The method for preparing the waterborne polyacrylic-epoxy resin (D) is not particularly limited, and any known method is applicable.

[0115] For example, epoxy resin reacts with at least a vinyl monomer containing a glycidyl group, a vinyl monomer containing an amide group or a vinyl monomer containing an amino group and a glycidyl ether of a polyalkylene glycol, and an amine is added as a catalyst to obtain a vinyl monomer containing a carboxyl group. The monomer and the vinyl monomer containing a carboxyl group are then polymerized. For vinyl monomers containing glycidyl groups, it can be used without restriction as long as its molecules contain a glycidyl group and a polymerizable vinyl group, including (methyl) glycidyl acrylate, (methyl) 3-methyl glycidyl acrylate and (methyl) allyl glycidyl ether. For vinyl monomers containing amide groups, it can be used without restriction as long as its molecules contain an amide group and a polymerizable vinyl group, including acrylamide, N-butoxymethyl (methyl) acrylamide, N-methyl (methyl) acrylamide, N, N-dimethyl (methyl) acrylamide, N-isopropyl (methyl) acrylamide, diacetone (methyl) acrylamide and N-vinyl formamide. The amino group-containing vinyl monomer contains an amino group and a polymerizable vinyl group in its molecule, including N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate.

[0116] In some embodiments of the present invention, the content of the polyacrylic-epoxy resin in the protective coating composition is 35 wt % to 60 wt % based on the total weight of the solid content in the protective coating composition.

[0117] The above-mentioned polyacrylic-epoxy resins may be used alone or in any combination.

[0118] Examples of commercially available polyurethane-acrylic resins are, for example, waterborne polyurethane-epoxy resin MR1487W from KDD functional material; GS-5000B, GS-500D from Guangxiu Chemical, and ACUST 3958 from Wuxi Honghui New Materials Technology.

[0119] Solvents

[0120] The protective coating composition of the present invention comprises a solvent, such as water, to dissolve all components, thereby forming a coating dispersion. Water is used to dilute the surface treatment composition of the present invention, and it provides relatively long-term stability for the composition. For example, under the same storage conditions, a composition having a water content of less than about 40% by weight is more likely to polymerize or "gel" than a surface treatment composition having a water content of about 60% by weight or more. Although the protective coating composition of the present invention generally applied to a substrate contains about 70% by weight or more water, such as 85% by weight, it should be understood that the protective coating composition of the present invention also includes a concentrated formulation composition having a water content of 50% to 85% by weight. The end user only needs to dilute the concentrated formulation with additional water to obtain the optimal protective coating composition concentration for a specific surface treatment application.

[0121] In some embodiments of the present invention, deionized water is preferably used as the solvent. In some embodiments of the present invention, the water content of the protective coating composition is 50 wt % to 85 wt %, or 60 wt % to 85 wt %, or 65 wt % to 75 wt %, based on the total weight of the protective coating composition.

[0122] The protective coating composition of the present invention may be provided as a ready-to-use protective coating composition, as a concentrated protective coating composition to be diluted with water before use, as a replenishing composition or as a multi-component coating system.

[0123] As used herein, "aqueous solution" means that the protective coating composition contains at least 50% by weight, or at least 60% by weight, or at least 65% by weight of water, based on the total weight of the composition. In addition to water, other suitable solvents include those particularly useful in waterborne coating technology. Examples of other suitable solvents include, but are not limited to: water-compatible solvents, such as alcohols or ethers, more specifically, methanol and ethanol; glycols, such as dipropylene glycol; and other glycol ethers, such as propylene glycol monobutyl ether and dipropylene glycol monobutyl ether.

[0124] pH value of protective coating compositions

[0125] The pH value of the protective coating composition is greater than 7 to 12, or 7.5 to 12, or 8 to 12, or 8.1 to 11.5. The lower limit of the pH value is 7.1, 7.5, 8.0, 8.1, 8.2, 8.5, 8.8, 9.0, 9.2, 9.5 or 10.0; the upper limit of the pH value is 12, or 11.8, or 11.6, or 11.5, or 11.2, or 11.0. If necessary, one or more optional pH adjusters, including small amounts of inorganic acids, alkaline components and organic acids, can be used to adjust the pH value to the above desired operating pH value. A protective coating composition with an alkaline operating pH value will produce better anti-corrosion effects.

[0126] The pH value of the aqueous protective coating composition is in the range of 7.1 to 12, preferably 8 to 12, in other words, the aqueous surface treatment solution according to the present invention is an alkaline solution.

[0127] Other additives

[0128] The protective coating composition of the present invention may also contain optional additives. The selection of suitable additives for the protective coating composition depends on the specific intended use and can be determined by those skilled in the art in each case. Optional additives include defoamers, sizing agents, matting agents, thickeners, inhibitors, pigments / fillers, etc.

[0129] <Wax>

[0130] The type of aqueous lubricant is not particularly limited, and examples thereof include polyolefin waxes such as polyethylene wax and polypropylene wax; paraffin waxes such as synthetic paraffin wax and natural paraffin wax; microcrystalline wax; and fatty acid amide compounds such as steer amide, palmitamide, methylenebisstearylamide and oleamide. The content of the aqueous lubricant / wax is preferably 0.1 to 20% by weight, more preferably 0.5 to 10% by weight, based on the solid content of the treatment agent. When the content of the aqueous lubricant is within the above range, the protective coating composition can provide a more excellent lubrication effect and a lower friction coefficient, which is advantageous.

[0131] <Inorganic inhibitors>

[0132] The zirconium compound is used as a film-forming component to form a three-dimensional cross-linked zirconium oxide coating by hydrolysis and condensation reaction, while accompanying the desorption of volatile acids in the aqueous system during the curing process, and can have a positive impact on corrosion resistance and adhesion to the substrate. The selected zirconium compound should be stable in an alkaline aqueous solution. The zirconium compound is not particularly limited in type, as long as it contains a zirconium atom, and examples thereof include basic zirconium carbonate, zirconium carbonate salts (such as sodium zirconium carbonate, potassium zirconium carbonate, lithium zirconium carbonate and ammonium zirconium carbonate), zirconium hydroxide, zirconium lactate, zirconium acetate, zirconium nitrate, zirconium sulfate, zirconium chloride, calcium zirconate, ethanol zirconium (zirconium ethoxide) and hexafluoroacetylaceton zirconium. Among them, in terms of excellent corrosion resistance, ammonium zirconium carbonate and sodium zirconium carbonate are preferred. The zirconium compound is selected from ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium oxide and zirconium acetate.

[0133] Wherein, the inorganic inhibitor is a metal compound, such as a vanadium compound. The metal material may have a three-dimensional shape, such as a structure made of a metal sheet. The metal compound containing metal atoms is not particularly limited in type as long as it contains a metal, and examples thereof include the above-mentioned metal oxides and / or metal alkoxides containing metal atoms. The supply source of metal ions can be at least one metal compound selected from ammonium salts and acetonates of, for example, Mo, W, Y, Bi, Mn, La, Ce, Sm, Zn, Al, Si, Ni, Co, Zr, Mg, Ti and V. Among them, compounds that can be dissolved in alkaline solutions are preferred. For example, vanadium compounds, such as vanadium pentoxide, vanadium trioxide, vanadium oxyacetyl acetonate, vanadium acetylacetonate, etc.

[0134] The content mass ratio of the metal material and the organosilane [M / silane] is 1 to 5, preferably 2 to 4. If the solid content mass ratio is less than 1, no corrosion resistance effect will be exhibited, while if the ratio is higher than 5, the system will have difficulty maintaining stability and chemical resistance will be negatively affected.

[0135] In the aqueous protective coating composition solution, the content of the inorganic inhibitor is 1.5 wt % to 5.0 wt %, or 2.0 wt % to 4.0 wt %, or 1.5 wt % to 4.0 wt %, or 2.0 wt % to 5.0 wt %, based on the weight of the solid content of the protective coating composition.

[0136] <Silane Compound>

[0137] The silane compound in the present invention includes a silanol group-containing compound, which is a hydrolyzate of an organosilicon compound having a glycidoxyl group. The hydrolysis of the organosilicon can be carried out in a pH range of 8 to 10. As a hydrolysis aid, alkaline materials such as ammonia water and organic amines are preferred because they evaporate during the coating formation process and are difficult to remain in the two-in-one primer-pretreatment coating composition.

[0138] The protective coating composition of the present invention further comprises a silane compound as a coupling agent. It is known in the art that a silane coupling agent can be added to a surface coating composition of a metal material to improve the adhesion of a coating formed on the metal surface.

[0139] There is no limitation on the silane coupling agent used in the two-in-one primer-pretreatment coating composition, as long as the silane coupling agent is compatible with the rare earth element-containing compound (eg, water-soluble zirconium salt and other components contained therein).

[0140] The silane coupling agent may have an amino functional group or an epoxy functional group. The amino or epoxy functional silane may contain a C2-C10 alkoxy group.

[0141] The silane coupling agent may have the general formula R1-Si-X3, wherein R1 is a reactive organic functional group, and at least one of X is a hydrolyzable group and the others are optionally substituted alkyl or aryl groups containing 1 to 10 carbon atoms. The hydrolyzable group may be selected from alkoxy, acyloxy, halogen or amine. For example, the alkoxy may be a C1-C6 alkoxy (e.g., a methoxy or ethoxy group); the acyloxy may be a phenoxy group; the halogen may be a chloride or a bromide.

[0142] R1 can be an optionally substituted alkyl or aryl group containing 1 to 10 carbon atoms, for example 2 to 10 carbon atoms. If R3 is a substituted alkyl or aryl group containing 1 to 10 carbon atoms, then R1 is preferably substituted with one or more amine or epoxy functional groups. In these cases, the silane coupling agent can be described as an amino-functional silane or an epoxy-functional silane, respectively.

[0143] Some exemplary epoxy-functional silanes include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0144] Suitably, R3 is an alkyl or aryl group containing 1 to 10 carbon atoms substituted by one or more amine groups, or an aryl group containing 5 to 10 carbon atoms (e.g., a phenyl group) substituted by one or more amine groups. The amine groups may be one or more primary amines, secondary amines or tertiary amine groups.

[0145] Suitable amine-functionalized silane coupling agents for use in the surface treatment composition of the present invention have the following structure: (R2-O)3-Si-R3-NH2, wherein R2 is an alkyl group containing 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, most preferably a methyl group, and R3 is an alkylene group containing 1 to 10 carbon atoms, optionally substituted with an amino group. Examples of amine-functionalized silane coupling agents are aminomethylaminopropyltrimethoxysilane ((MeO)3-Si-(CH2)3-NH-(CH2)-NH2), aminopropyltrimethoxysilane ((MeO)3-Si-(CH2)3-NH2) and / or aminopropyltriethoxysilane ((EtO)3-Si-(CH2)3-NH2).

[0146] Other examples of silane coupling agents suitable for use in the present invention include, but are not limited to, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltri(2-ethylhexyloxy)silane, N -(6-aminohexyl)aminopropyltrimethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, o-aminophenyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane, aminopropyltriethoxysilane, aminopropylmethyldiethoxysilane, aminophenyltrimethoxysilane, 4-amino-3-dimethylbutyltrimethoxysilane, 4-amino-3-dimethylbutylmethyldimethoxysilane, 4-amino-3-dimethylbutyltriethoxysilane, 4-amino-3-dimethylbutylmethyl Diethoxysilane, N-phenyl-aminopropyl trimethoxysilane, N-naphthyl-aminopropyl trimethoxysilane, N-phenyl-aminopropyl methyl dimethoxysilane, N-naphthyl-aminopropyl methyl dimethoxysilane, N-(n-butyl)aminopropyl trimethoxysilane, N-(n-butyl)aminopropyl methyl dimethoxysilane, N-ethyl-aminopropyl trimethoxysilane, N-ethyl-aminopropyl methyl dimethoxysilane, N-methyl-aminopropyl trimethoxysilane, N-methyl-γ-aminopropyl methyl dimethoxysilane, N-β-(aminoethyl)-aminopropyl trimethoxysilane, N-β-(aminoethyl)-aminopropyl triethoxysilane silane, N-β-(aminoethyl)aminopropylmethyldimethoxysilane, N-β-(aminoethyl)aminopropylmethyldiethoxysilane, N-3-[amino(tripropyleneoxy)]aminopropyltrimethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, (3-trimethoxysilylpropyl)diethylenetriamine, (aminoethylamino)-3-isobutyldimethylmethoxysilane, (cyclohexylaminomethyl)triethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, (phenylaminomethyl)methyldimethoxysilane, 11-aminoundecyltriethoxysilane, 2-(2-pyridylethyl)thiopropyltrimethoxysilane, 2-(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, 3-(2-imidazolin-1-yl)propyltriethoxysilane, 3-(m-aminophenoxy)propyltrimethoxyaminopropylsilanetriol, 3-(m-aminophenoxy)propyltrimethoxysilane, 3-(N,N ... 3-(N-allylamino)propyltrimethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, 4-aminobutyltriethoxysilane, acetamidopropyltrimethoxysilane, aminopropylsilanetriol, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, bis(methyldiethoxysilylpropyl)amine, bis(methyldimethoxymethyl)silane Silylpropyl) n-methylamine, bis(triethoxysilylpropyl)amine, bis(trimethoxysilylpropyl)urea, bis[(3-trimethoxysilyl)propyl]ethylenediamine, bis[3-(triethoxysilyl)propyl]urea, diethylaminomethyltriethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, n-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyl trimethoxysilane, N-(3-aminopropyldimethylsilyl)aza-2,2-dimethyl-2-silacyclopentane, N-(3-triethoxysilylpropyl)4,5-dihydroimidazole, N-(3-trimethoxysilylpropyl)pyrrole, N-(6-aminohexyl)aminomethyltriethoxysilane, N-(6-aminohexyl)aminomethyltrimethoxysilane, N,N,N-trimethyl-3-(trimethoxysilyl)-1-propanaminium, N,N-dioctyl-N'-triethoxysilylpropyl urea, N-[5-(trimethoxysilyl)-2-aza-1-oxopentyl] caprolactam, N-3-[(amino(polypropyleneoxy)]aminopropyl trimethoxysilane, N-butylaminopropyl trimethoxysilane, N-cyclohexylaminopropyl trimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, N-ethylaminoisobutyltrimethoxysilane, N-phenylaminomethyltriethoxysilane, n-trimethoxysilylpropylcarbamoylcaprolactam, ureapropyltriethoxysilane, ureapropyltrimethoxysilane and mixtures thereof, preferably selected from N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, bis[3-(trimethoxysilyl)propyl]amine,

[0147] The amine-functional silane coupling agent and / or the epoxy-functional silane coupling agent may be used alone or in combination of two or more.

[0148] In the aqueous protective coating composition solution, the content of the silane coupling agent is 1.0 wt % to 4.5 wt %, or 1.4 wt % to 4.0 wt %, or 1.5 wt % to 3.5 wt %, or 1.4 wt % to 3.0 wt %, or 1.4 wt % to 2.5 wt %, based on the total weight of the solid content of the protective coating composition.

[0149] The solid content mass ratio of the silane compound and the zirconium compound (converted to Zr) is 0.1 to 3, preferably 0.2 to 1.5. When the mass ratio is too low, corrosion resistance cannot be achieved. When the mass ratio exceeds 3, stability and adhesion will be negatively affected.

[0150] <Fillers / Pigments>

[0151] As fillers / coloring pigments, known inorganic and organic coloring pigments can be used. As inorganic pigments, titanium oxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO2), calcium carbonate (CaCO3), barium sulfate (BaSO4), aluminum oxide (Al2O3), kaolin, carbon black and iron oxide (Fe2O3 and Fe3O4) can be used. As organic pigments, Hanser yellow and pyrazolone orange pigments can be used. They are used to improve the appearance performance after applying the topcoat coating, and there is no special restriction. However, the particle size of the powder should be controlled below 10μm, preferably below 3μm. The weight ratio of pigment / filler to organic polymer resin is 0.05 to 1.0. When the ratio is too low, the covering ability cannot meet the appearance requirements (color difference and gloss); if the ratio is higher than 1.0, the filler will be severely precipitated and have a negative impact on the appearance.

[0152] <Other additives>

[0153] The coating composition / solution may optionally include conventional additives known to those skilled in the art of adhesives. Conventional additives compatible with the disclosed surface treatment composition / solution can be determined simply by combining potential additives with the composition and determining whether they remain uniform. Non-limiting examples of suitable additives include, but are not limited to, solvents, corrosion inhibitors, defoamers, surfactants, UV stabilizers, extenders, plasticizers, and pigments known in the art.

[0154] The total content of additives will vary depending on the amount of each specific additive required to provide a coating composition / solution for light metal materials having the desired properties. The content of additives can be from 0 to about 10 weight %, preferably from about 0.1 to about 5 weight %, of the total weight of the protective coating composition.

[0155] Preparation method of bifunctional epoxy resin precursor

[0156] The bifunctional epoxy resin precursor can be prepared by repeating the addition reaction and condensation reaction of the bifunctional epoxy. The epoxy of the present invention is not particularly limited in type as long as it contains two epoxy groups in its molecule, including bisphenol A, bisphenol F and epichlorohydrin (epichlorohydrin) (e.g., epihalohydrin) and epoxy compounds with two or more glycidyl groups.

[0157] In some embodiments of the present invention, the difunctional epoxy resin precursor is preferably prepared by the following steps:

[0158] The difunctional epoxy is reacted with a nucleophilic or electrophilic compound having an active hydrogen atom; and a pH adjuster and water are added to the solution to obtain a neutralized difunctional epoxy resin precursor having a solid content of 5 to 32 weight percent.

[0159] In some embodiments of the present invention, the difunctional epoxy resin precursor is represented by the formula:

[0160] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2

[0161] Among them, independently,

[0162] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms;

[0163] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms (preferably 1 to 10 carbon atoms) or H;

[0164] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms;

[0165] X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-, preferably -COO-, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- comprises an aliphatic chain having 1 to 5 carbon atoms;

[0166] Y = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-, preferably -COO-, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- comprises an aliphatic chain having 1 to 5 carbon atoms;

[0167] R3 is any type of chain as long as it connects two hydroxyl α-carbon atoms; preferably, R3 is selected from the group consisting of: aromatic or aliphatic groups having 1 to 20 carbon atoms, polyurethane groups, aliphatic or aromatic alkanes having 2 to 20 carbon atoms, and acrylate-containing polymer groups.

[0168] n is an integer of 1-10, preferably an integer of 2-8.

[0169] Method for preparing protective coating composition

[0170] The protective coating composition can be prepared by dispersing all resin materials, inorganic inhibitors, silane coupling agents and other raw materials (including color pigments) in water or a water-soluble solvent. The solid content is adjusted by removing the solvent and volatile components. The solvent is usually water, and some small amounts of water-based solvents (such as alcohols, ketones, and water-soluble organic solvents based on cellosolves) can be used in combination to reduce the film-forming time. The solid content concentration of the aqueous protective coating composition is not particularly limited, but is preferably in the range of 15% to 50% by weight, or 15% to 40% by weight, or 25% to 35% by weight.

[0171] The method for forming the intermediate layer is not particularly limited. For example, a roll coater, dipping and spraying, followed by drying by a hot air furnace, an induction heating furnace and an infrared heater. The peak temperature of the steel sheet is 40-150°C, but preferably in the range of 50 to 80°C.

[0172] In some embodiments of the present invention, the protective coating composition is preferably prepared by the following steps:

[0173] a) dissolving the resin compound and other compounds in water under stirring to obtain a solution;

[0174] b) adjusting the solution obtained in step a) by an ammonia solution so that the solution reaches an appropriate pH value, the pH value of the solution is preferably 8 to 12, preferably greater than 9 to 12, or more preferably 9 to 10;

[0175] c) Add the silane coupling agent under stirring to achieve a balance between hydrolysis and condensation.

[0176] d) Add wax when necessary and stir to obtain a homogeneous solution without stratification.

[0177] Aluminum alloy surface coating and curing method

[0178] The method according to the invention is particularly suitable for coating metal sheets selected from zinc or zinc alloy sheets, aluminum or aluminum alloy sheets, and steel strips coated with zinc or zinc alloys or coated with aluminum or aluminum alloys. Here, "zinc alloy" or "aluminum alloy" is understood to mean an alloy consisting of more than 50 atomic % zinc or aluminum.

[0179] For the test plate, the following materials (i) to (ii) were used.

[0180] i. Electrogalvanized steel sheet (EG): sheet thickness 0.8 mm; coating weight 40 / 20 g / m 2 ;

[0181] ii. Galvanized steel sheet (GA): sheet thickness 0.8mm; coating weight 90 / 45g / m 2 .

[0182] The test plate was processed according to the following steps (1) to (5).

[0183] 1) Degrease the metal surface of the test plate;

[0184] 2) Rinse with tap water;

[0185] 3) Dry the metal surface with compressed air;

[0186] 4) rolling the coating composition onto the surface of the test plate;

[0187] 5) drying the coating composition by passing it through hot air or in an oven,

[0188] Therein, during step (5), the temperature is preferably at least 75°C, but not more than 240°C, preferably not more than 150°C.

[0189] In some embodiments of the present invention, the coating composition for treating a metal plate is applied to a new surface of the metal plate using a bar coater, and the test plate is dried in a hot air dryer so that the peak metal temperature (PMT) of the test plate is 95°C.

[0190] Coating Thickness Measurement

[0191] When measuring the coating thickness, a cross-sectional sample was first made using an X-ray spectrometer (ZSX PrimusⅢ+; Rigaku Corporation, Japan). Three points on the panel were selected to test the coating thickness. The minimum value was the lower limit, and the maximum value was the upper limit.

[0192] The dry film thickness is 0.5-4.0 μm. The preferred film thickness is 1.0-3.0 μm.

[0193] Formation of topcoat layer

[0194] After forming the primary coating (cured protective coating composition), the topcoat material was applied to a dry thickness of 15 μm using a bar coater, and then the sample was heat-dried in a hot air drying oven to a peak plate temperature of 230° C. The topcoat was selected from a domestic polyurethane coating from Nippon.

[0195] List of implementation plans

[0196] 1. A protective coating composition comprising:

[0197] a) at least one resin selected from the group consisting of a polyurethane resin (A) and a polyurethane-acrylic resin (B);

[0198] b) water; and

[0199] c) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula:

[0200] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2

[0201] Among them, independently,

[0202] X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;

[0203] Y=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;

[0204] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H;

[0205] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms;

[0206] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4;

[0207] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;

[0208] n is an integer of 1 to 10.

[0209] 2. The protective coating composition of embodiment 1, wherein independently, R2 is an aromatic or aliphatic chain having 1 to 10 carbon atoms or H, R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, R1 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, -XH or -X-R4.

[0210] 3. The protective coating composition according to any one of the preceding embodiments, wherein R3 is selected from the group consisting of an aromatic or aliphatic group having 1 to 20 carbon atoms, a polyurethane group, an aliphatic or aromatic alkane having 2 to 20 carbon atoms, and an acrylate-containing polymer group.

[0211] 4. The protective coating composition according to any one of the preceding embodiments, wherein X is selected from -COO-, -P(OR)(OH)-O-; and n is an integer from 2 to 8.

[0212] 5. The protective coating composition according to any one of the preceding embodiments, wherein the difunctional epoxy resin precursor (C) is represented by the following formula:

[0213] (H)X-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H

[0214] Among them, independently,

[0215] X=-COO-, -P(OR)(OH)-O-;

[0216] R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms;

[0217] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;

[0218] n is an integer of 2-8.

[0219] 6. The protective coating composition according to claim 1, wherein the content of component c) is 4.5 wt% to 35 wt%, preferably 4.5 wt% to 23 wt%, more preferably 8.5 wt% to 18.5 wt%, based on the total weight of solid content in the protective coating composition.

[0220] 7. The protective coating composition according to claim 1, wherein the content ratio of the bifunctional epoxy resin precursor (C) to the total mass of the polyurethane-acrylic resin (B), the polyurethane resin (A), the polyacrylic-epoxy resin (D) and the bifunctional epoxy resin precursor (C) is 7.0 wt % to 30 wt %, preferably 10.5 wt % to 27.0 wt %.

[0221] 8. The protective coating composition according to any one of the preceding embodiments, further comprising a polyacrylic-epoxy resin (D).

[0222] 9. The protective coating composition according to any one of the preceding embodiments, wherein the protective coating composition further comprises 1.0 wt % to 4.5 wt %, preferably 1.4 wt % to 2.5 wt %, based on the total weight of the solid content, of a resin containing a silanol group, wherein the resin containing a silanol group is represented by the following formula XY(Z): n Si(OH) 3-n express,

[0223] Wherein, independently, X is a glycidoxy group or a functional group derived from a glycidoxy group, Y is a C1 to C10 alkylene group, Z is a methoxy group, an ethoxy group or a methyl group, and n is an integer from 0 to 2.

[0224] 10. The protective coating composition according to any one of the preceding embodiments, further comprising 0.1 to 3 wt% of a wax, based on the total weight of the protective coating composition.

[0225] 11. The protective coating composition according to any one of the preceding embodiments, further comprising 1 to 20 wt% of a filler, based on the total weight of the solid content in the composition.

[0226] 12. The protective coating composition according to any one of the preceding embodiments, further comprising 1.5 to 5.0 wt. % of a metal inhibitor, based on the total weight of the solid content in the composition, wherein the metal inhibitor comprises a zirconium compound selected from the group consisting of ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium carbonate, zirconium acetate, and combinations thereof.

[0227] 13. The protective coating composition according to any one of the preceding embodiments, wherein the pH value of the protective coating composition is greater than 7 to 12.

[0228] 14. The protective coating composition according to any one of the preceding embodiments, wherein the pH value of the protective coating composition is equal to or greater than 8 to 10.

[0229] 15. The protective coating composition according to any one of the preceding embodiments, wherein the solids content of the protective coating composition is from 15 wt% to 50 wt%, based on the total weight of the protective coating composition.

[0230] 16. The protective coating composition according to any one of the preceding embodiments, wherein the solids content of the protective coating composition is from 25 wt% to 35 wt%, based on the total weight of the protective coating composition.

[0231] 17. A method for providing corrosion protection and enhancing coating adhesion on a metal surface, the method comprising the steps of:

[0232] a) contacting the protective coating composition according to any one of embodiments 1 to 16 with a metal surface at a process temperature of at least 40° C. but not higher than 200° C., thereby forming a film on the metal surface;

[0233] b) optionally removing excess of the protective coating composition from the surface; and

[0234] c) curing the film on the surface by thermal means or high energy irradiation at a process temperature of 50-90° C. for at least 10 −5 seconds to form a cured coating.

[0235] 18. The method according to embodiment 17, wherein the layer thickness of the cured coating is at least 0.5 μm but not more than 4.0 μm.

[0236] 19. An article comprising at least a portion of the treated metal surface of embodiment 17.

[0237] 20. The article according to embodiment 19, wherein the layer thickness of the protective coating is at least 0.5 μm but not more than 4.0 μm.

[0238] 21. According to the product described in any one of embodiments 19-20, the T-bend value (new) of the treated metal surface when tested according to GB / T13448-2006 standard is equal to or less than 1T, and the T-bend value (aged, after aging for 24 hours at a temperature of 50±2°C and a humidity of 95%) when tested according to GB / T13448-2006 standard is equal to or less than 2T.

[0239] 22. An article, at least a portion of which comprises a protective coating, wherein the protective coating is the cured product of the protective coating composition according to any one of embodiments 1 to 16.

[0240] 23. The article according to embodiment 22, wherein the layer thickness of the protective coating is at least 0.5 μm but not more than 4.0 μm.

[0241] Example:

[0242] The present invention will be further described and illustrated in detail with reference to the following examples. These examples are intended to help those skilled in the art to better understand and practice the present invention, but are not intended to limit the scope of the present invention. Unless otherwise stated, all numerals in the examples are by weight.

[0243] raw materials

[0244]

[0245]

[0246] *All raw materials are used directly without any special treatment.

[0247] Example 1

[0248] <Preparation of bifunctional epoxy resin precursor>

[0249] The bifunctional epoxy resin precursor C1 was synthesized by the following steps:

[0250] Adipic acid and 40 g of propylene glycol monomethyl ether were placed in a 100 ml round-bottom four-necked flask and heated at 90° C. Then 260 g of A-type epoxy liquid resin YD-128A (from Guodu) with an epoxy equivalent of 190 was slowly added, and the temperature was maintained at 95° C. for 2 hours. After the reaction, 180 g of a 28 wt % ammonia solution was slowly added at 40° C., and then water was added to obtain an ammonia-neutralized bifunctional epoxy resin precursor C1 with a solid content of 5%-32%. The weight average molecular weight of the bifunctional epoxy resin precursor C1 was 13,000.

[0251] The bifunctional epoxy resin precursor C2 was synthesized by the following steps:

[0252] Orthophosphoric acid and 100 g of propylene glycol monomethyl ether were slowly added to 1250 g of type A epoxy resin with an epoxy equivalent of 500, and kept at 95° C. for 2 hours. After the reaction, 40 g of a 28% ammonia solution was slowly added at 140° C., and then water was added to obtain an ammonia-neutralized phosphoric acid-modified bifunctional epoxy resin precursor C2 with a solid content of 5% to 32%. The weight average molecular weight of the bifunctional epoxy resin precursor (C2) was 20,000.

[0253] <Preparation of Protective Coating Composition>

[0254] The protective coating composition is prepared by the following steps:

[0255] a) adding 45 g of Hauthane L-3528 (liquid, from Hauthaway), 8 g of a difunctional epoxy resin precursor (prepared as described above), 0.5 g of Dynasylan GLYEO (liquid, from Evonik), and 0.6 g of zirconium (IV) acetate (liquid, from Sinopharm chemical reagent Co., Ltd), and mixing them to form an aqueous dispersion;

[0256] b) 12 g of Rutile R996 (liquid from Yuejiang) were added to the aqueous dispersion prepared in step a).

[0257] <Aluminum Alloy Surface Coating and Curing>

[0258] Test Materials

[0259] Galvanized steel sheet (GA): sheet thickness 0.8 mm; coating weight 90 / 45 g / m 2 ;

[0260] The electroless metal surface treatment process preferably includes the following subsequent steps (1)-(5):

[0261] 1) Degrease the metal surface using RIDOLINE 1559 degreaser from Henkel;

[0262] 2) Rinse with tap water;

[0263] 3) Dry the metal surface with compressed air;

[0264] 4) Roller-coat the primer / pretreatment agent on the substrate;

[0265] 5) Curing by hot air / oven,

[0266] Wherein, during step (5), the temperature is about 85°C.

[0267] The protective coating composition was applied onto a new substrate using a doctor blade coater and dried in a hot air dryer, such that the peak metal temperature (PMT) of the test panel was 95 °C.

[0268] When measuring the coating thickness, cross-section samples were first prepared using an X-ray spectrometer (ZSX Primus Ⅲ+; Rigaku Corporation, Japan). Three points on the panel were cut / selected to test / detect the coating thickness. The minimum value was the lower limit and the maximum value was the upper limit.

[0269] The dry film thickness ranged from 1.2 μm to 1.7 μm.

[0270] After the primary layer was formed, the topcoat material was applied using a doctor blade coater to a dry thickness of 15 μm. Next, the sample was heated and dried in a hot air drying oven to a peak plate temperature of 230 °C. The topcoat used was a household polyurethane paint from Nippon.

[0271] Examples 2-18 and CE1-CE19

[0272] The coating compositions of E2 to E18 and CE1 to CE19 were prepared with reference to Example 1. The metal surfaces of E2 to E18 and CE1 to CE19 were treated with reference to Example 1. More details are listed in the results section below.

[0273] Various tests were conducted on the prepared samples.

[0274] Test Method

[0275] Adhesion

[0276] <T-bend value (new)> and <T-bend value (aged)>

[0277] According to the requirements of the bending test method in GB / T 13448-2006 "Test Methods for Color Coated Steel Sheets and Strips", a 180-degree bending test was carried out using a T-type bending testing machine. At the same time, the sample was placed in a test chamber with the temperature set at 50 ± 2 °C and the humidity at 95%, and an accelerated aging test was conducted for 24 hours. After taking out the sample, a T-type bending test (aged T-bend value) was carried out. The T-type bending test equipment was the WZJ-II T-type bending machine from Shanghai Xiandai Environment Engineering Technique Co., Ltd.

[0278] The results of the T-bend value (new) were recorded and ranked as follows:

[0279] - Unqualified: greater than 1T.

[0280] - Qualified: less than or equal to 1T.

[0281] -Good: equal to 0T.

[0282] The T-bend value (aging) results are recorded and ranked as follows:

[0283] - Unqualified: greater than 2T.

[0284] -Qualified: less than or equal to 2T.

[0285] - Good: less than or equal to 1T.

[0286] -Excellent: equal to 0T.

[0287] <Cross-cupping test>

[0288] According to the requirements of the bending test in GB / T13448-2006 "Test Methods for Color Coated Steel Sheets and Strips", a cross-cutting-cupping test was performed using a cupping tester, which is an electro-hydraulic cupping tester Cat. No. 5400 from BYK-Gardner GmbH.

[0289] The results of the cross-hatch-cupping test were recorded and ranked as follows:

[0290] Failure (F): The peeling area is greater than 5%.

[0291] Pass (P): The peeling area is less than or equal to 5%.

[0292] Good (G): The peeling area is less than or equal to 2%.

[0293] Very good (VG): The peeled area is equal to 0%.

[0294] <Reverse impact test>

[0295] The reverse impact test is to drop a weight onto the strip from a height of 3 times the thickness of the metal. Check if the coating on the deformed surface is cracked or broken. Then apply tape to the deformed area and remove it. If any coating is removed from the surface of the strip, the sample fails the test. The energy impact tester is Elcometer 1615. The weight of the weight is 1Kg, the height is 90cm, and the impact energy is 9J.

[0296] Evaluation criteria:

[0297] Good (G): The paint layer is not peeling and there are no cracks.

[0298] Unqualified (F): There are cracks or paint peeling.

[0299] Corrosion resistance

[0300] <Cross neutral salt spray test 240 hours>

[0301] Each test panel (150mm X 70mm) with a cross "X" cut was tested by a neutral salt spray test (GBT10125-1997), 240 hours for home applications and 1000 hours for building applications. The length of the cutting line exceeds 50mm. The expansion width (maximum value) of the cross line was measured and evaluated according to the following standards. The corrosion test equipment is the Q-fog SSP salt spray test chamber of Q-Lab. Trimming guard: in accordance with the 10th level requirements of GB / T6461 standard.

[0302] Very good (VG): less than or equal to 1mm.

[0303] Good (G): less than or equal to 2 mm.

[0304] Pass (P): less than or equal to 3mm.

[0305] Unqualified (F): greater than 3mm.

[0306] <500 hours neutral salt spray test on board>

[0307] Each test panel (150 mm x 70 mm) was subjected to a neutral salt spray test (GBT10125-1997) for 500 hours (domestic application), and visually inspected and evaluated as follows.

[0308] Evaluation criteria:

[0309] Very Good (VG): No bubbles.

[0310] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.

[0311] Pass (P): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.

[0312] Failure (F): The size of a single bubble is equal to or greater than 1.0 mm, and the number of bubbles generated is equal to or greater than 10 and less than 20.

[0313] <Scrap edge neutral salt spray test 240 hours>

[0314] Each test panel (150 mm x 70 mm) with a cut edge was subjected to a neutral salt spray test (GBT10125-1997) for 240 hours (for home use), and visually inspected and evaluated as follows.

[0315] Evaluation criteria:

[0316] Very good (VG): less than or equal to 3mm.

[0317] Good (G): less than or equal to 6 mm.

[0318] Pass (P): greater than 6mm and less than 10mm.

[0319] Failure (F): equal to or greater than 10mm.

[0320] Solvent resistance

[0321] <Surface resistance to solvent wiping (MEK)>:

[0322] The equipment is a DJH MEK friction tester from DJH Designs Inc., with a set speed of 1 round trip per second, a pressure of 0.1±0.02Mpa, and a test length of not less than 150mm.

[0323] Evaluation criteria:

[0324] Good (G): No marks, or traces of wiping without paint peeling.

[0325] Unqualified (P): The topcoat is peeling off.

[0326] Chemical resistance

[0327] <Alkali resistance>

[0328] Each test plate was immersed in a 5 wt% NaOH aqueous solution at room temperature for 24 hours. The size and density of generated bubbles were then visually inspected, and alkali resistance was evaluated in the following manner.

[0329] Evaluation criteria:

[0330] Very Good (VG): No bubbles.

[0331] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.

[0332] Pass (P): The single bubble size is 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.

[0333] Failure (F): The size of a single bubble is 1.0 mm or larger, or the number of bubbles generated is greater than 10.

[0334] <Sulfuric acid resistance test> and <Hydrochloric acid resistance test>

[0335] Each test plate was immersed in a 5 wt % aqueous sulfuric acid solution at room temperature for 24 hours, and then the size and density of generated bubbles were visually inspected and evaluated based on a standard similar to that of alkali resistance.

[0336] Each test plate was immersed in a 5 mass % hydrochloric acid aqueous solution at room temperature for 24 hours, and then the size and density of generated bubbles were visually inspected and evaluated based on criteria similar to those for alkali resistance.

[0337] Very Good (VG): No bubbles.

[0338] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.

[0339] Pass (P): The single bubble size is 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.

[0340] Failure (F): The size of a single bubble is 1.0 mm or larger, or the number of bubbles generated is greater than 10.

[0341] Appearance

[0342] <Glossiness>

[0343] Gloss is measured with a gloss meter. The gloss meter illuminates the surface of the coating to confirm that the coating gloss is within the set range (standard ± 5). The gloss meter is BYK 4563 from BYK-Gardner GmbH.

[0344] Evaluation criteria:

[0345] Good (G): Deviation from the standard is less than 3.

[0346] Failure (F): Deviation from the standard is equal to or greater than 3.

[0347] <Color difference>

[0348] The color difference is measured with a color difference device that illuminates the coating surface to confirm that the color difference is within a set range (standard ±5). The color difference device is HunterLab Agera from Eutin International Trading Co., Ltd.

[0349] Evaluation criteria:

[0350] Good (G): The range is equal to or less than 3.

[0351] Failure (F): The range is greater than 3.

[0352] hardness

[0353] <Topcoat pencil hardness>

[0354] The hardness of the topcoat / clearcoat was tested according to GB / T6739-2006. The instrument was TQC VF2378 from HJ Unkel (Shanghai) International Trading Co., Ltd.

[0355] Qualified: Same as or harder than HB (GB / T6739-2006, China Pencil 101).

[0356] Unqualified: Softer than HB.

[0357] result

[0358] Table 1

[0359]

[0360] Table 1 shows the compositions of the protective coating compositions E1-E13.

[0361]

[0362] Table 2 shows the test results of the protective coating compositions E1-E13.

[0363] In Examples 1 to 13, the protective coating composition is prepared according to the formula provided by the present invention and has good adhesion performance, and even after aging, the adhesion performance still meets the requirements. In addition, E1-E13 has excellent anti-corrosion performance.

[0364] Table 3

[0365] CE1 CE2 CE3 CE4 Esacote PU A32D 17.5 12.5 12.5 11.5 BS PUAW TT-10 C1 1 6 7 10 JH-O1871 0.5 0.5 0.5 Dynasylan GLYEO 0.5 Zircosol AC 20 0.6 0.6 0.6 Zirconium(IV) acetate 0.6 Vanadium(V) oxide (99%) 0.2 Vanadium acetylacetonate (3) 0.2 0.2 0.2 Rutile R996 6 6 6 Pigment White 18 6 Total solids 25.8 25.8 26.8 28.8 Total composition 100 100 100 100

[0366] Table 3 shows the compositions of Comparative Examples CE1-CE4.

[0367] Table 4.

[0368]

[0369] Table 4 shows the test results of Comparative Examples CE1-CE4.

[0370]

[0371]

Claims

1. A protective coating composition comprising: d) at least one resin selected from the group consisting of a polyurethane resin (A) and a polyurethane-acrylic resin (B); e) solvent; and f) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula: R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2 in, Independently, X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; Y=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H; R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms; R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4; R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms; n is an integer of 1 to 10.

2. The protective coating composition according to claim 1, wherein Independently, R2 is an aromatic or aliphatic chain having 1 to 10 carbon atoms or H, R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, R1 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, -XH or -X-R4.

3. The protective coating composition according to claim 1, wherein R3 is selected from the group consisting of an aromatic or aliphatic group having 1 to 20 carbon atoms, a polyurethane group, an aliphatic or aromatic alkane having 2 to 20 carbon atoms, and an acrylate-containing polymer group.

4. The protective coating composition according to claim 1, wherein X is selected from -COO-, -P(OR)(OH)-O-; and n is an integer from 2 to 8.

5. The protective coating composition according to claim 1, wherein: The bifunctional epoxy resin precursor (C) is represented by the following formula: (H)X-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H Among them, independently, X=-COO-, -P(OR)(OH)-O-; R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms; R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms; n is an integer of 2-8.

6. The protective coating composition according to claim 1, wherein: The content of component c) is 4.5% to 35% by weight, based on the total weight of the solid content in the protective coating composition.

7. The protective coating composition according to claim 1, wherein: The content ratio of the bifunctional epoxy resin precursor (C) to the total mass of the polyurethane-acrylic resin (B), the polyurethane resin (A), the polyacrylic-epoxy resin (D) and the bifunctional epoxy resin precursor (C) is 7.0 wt % to 30 wt %.

8. The protective coating composition according to claim 1, wherein: The protective coating composition further comprises a polyacrylic-epoxy resin (D).

9. The protective coating composition according to claim 1, wherein: The protective coating composition further comprises 1.0 wt % to 4.5 wt % of a silanol group-containing resin, based on the total weight of the solid content, wherein the silanol group-containing resin is represented by the following formula XY(Z): n Si(OH) 3-n express, Wherein, independently, X is a glycidoxy group or a functional group derived from a glycidoxy group, Y is a C1 to C10 alkylene group, Z is a methoxy group, an ethoxy group or a methyl group, and n is an integer from 0 to 2.

10. The protective coating composition according to claim 1, wherein: The protective coating composition further comprises 0.1 to 3 wt % of a wax, based on the total weight of the protective coating composition.

11. The protective coating composition according to claim 1, wherein: The protective coating composition further comprises 1 to 20 wt % of a filler, based on the total weight of the solid content of the composition.

12. The protective coating composition according to claim 1, wherein: The protective coating composition further comprises 1.5 to 5.0 wt % of a metal inhibitor, based on the total weight of the solid content in the composition, the metal inhibitor comprising a zirconium compound selected from the group consisting of ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium carbonate, zirconium acetate, and combinations thereof.

13. The protective coating composition according to claim 1, wherein: The protective coating composition has a pH value of greater than 7 to 12.

14. The protective coating composition according to claim 1, wherein: The protective coating composition has a pH value of 8 to 10, which is equal to or greater than 8.

15. The protective coating composition according to claim 1, wherein: The protective coating composition has a solid content of 15 wt % to 50 wt % based on the total weight of the protective coating composition.

16. The protective coating composition according to claim 1, wherein: The protective coating composition has a solid content of 25 wt % to 35 wt % based on the total weight of the protective coating composition.

17. A method for providing corrosion protection and enhancing coating adhesion on a metal surface, the method comprising the steps of: a) contacting the protective coating composition according to any one of claims 1 to 16 with a metal surface at a process temperature of at least 40° C. but not higher than 200° C., thereby forming a film on the metal surface; b) optionally removing excess of the protective coating composition from the surface; as well as c) curing the film on the surface by thermal means or high energy irradiation at a process temperature of 50-90° C. for at least 10 −5 seconds to form a cured coating.

18. The method according to claim 17, wherein: The layer thickness of the cured coating is at least 0.5 μm but not more than 4.0 μm.

19. An article comprising at least a portion thereof comprising the treated metal surface of claim 17.

20. The article of claim 19, wherein: The layer thickness of the protective coating is at least 0.5 μm but not more than 4.0 μm.

21. The product according to claim 20, wherein the T-bend value (new) of the treated metal surface when tested according to GB / T13448-2006 standard is equal to or less than 1T, and the T-bend value (aged, after aging for 24 hours at a temperature of 50±2°C and a humidity of 95%) when tested according to GB / T13448-2006 standard is equal to or less than 2T.

22. An article, at least a portion of which comprises a protective coating, wherein: The protective coating is a cured product of the protective coating composition according to any one of claims 1 to 16.

23. The article of claim 22, wherein: The layer thickness of the protective coating is at least 0.5 μm but not more than 4.0 μm.

Citation Information

Patent Citations

  • Chromium-free coil coating composition

    DE19751153A1

  • chrome-free anti-corrosion agent and anti-corrosion process

    DE19754108A1

  • Polymerizable composition for the anticorrosion coating of metallic substrates contains an organic titanium, silicon or zirconium compound

    DE19923118A1